Spatial Planning and Strategies of Medical Tourism Development towards the Expansion of Health Villages (A Case Study of Health Region No.2) - Sayedeh Somayeh Hosseini; Massoud Taghvaei (برنامه‌ریزی توسعه شهری و منطقه‌ای, 2019)
Many governments around the world are highly interested in the expansion of medical tourism industry as a national strategic industry, and as one form of health services trade and try to plan for it. Considering Iran’s capabilities in this industry, the present research aimed to compile/develop and prioritize the strategies of medical tourism development of health region No.2 taking the approach of service integration towards the development of health villages.  In the first phase, the data were gathered from a number of key experts by using documentary- analysis method (content analysis approach), interview and survey. Data analysis was done by using MAXQDA-18 software.  In the second phase, the data obtained from the previous phase was examined by SWOT technique. Thereafter, by combining two techniques of SWOT and fuzzy DEMATEL towards research objectives, different types of strategies were determined and prioritized by AHP technique. Statistical population under study in the evaluation and prioritization phase included 20 subjects/participants selected from the health tourism experts of Azerbaijan Region.  The results obtained from the integration of multi-criteria decision-making techniques and SWOT model revealed that offensive strategies (SO), review (revision) strategies (WO), defensive strategies (WT) and diversity strategies ranked first to fourth in terms of priority.